Tractor owner-operators in Nigeria: Insights from a small survey in Kaduna and Nasarawa states - Takeshima, Hiroyuki; Edeh, Hyacinth O.; Lawal, Akeem; Isiaka, Moshud (International Food Policy Research Institute, 2014)
This paper presents results of a small survey of tractor owner-operators conducted in Kaduna and Nasarawa states in Nigeria. Following are the key findings from simple descriptive statistics: (1) owner-operators who buy tractors from the private market or from private individuals are more efficient than those who receive tractors through government programs, providing services to a greater area at lower costs, including during the off-peak season; (2) providing access to a wider range of tractor horsepowers may improve efficiency over diverse soil types; (3) similar to some Asian countries in the 1980s, tractor operations are mostly concentrated in interviewees’ local home districts, though a fraction form groups and serve in distant locations to earn greater revenues.